2012
DOI: 10.1096/fasebj.26.1_supplement.911.3
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic bioreactor for epithelial cell studies under fluid shear stress

Abstract: We have developed a multilayer microfluidic bioreactor to evaluate polarized epithelial cell behavior under controlled fluid shear stress. The system consists of two microfluidic chambers separated by a synthetic porous membrane which provides a substrate for cell grown and allows apical to basolateral solute transport. The system has been used to evaluate a number of shear stress‐dependent cellular behaviors in kidney epithelial cells. We found that primary human renal epithelial cells undergo cytoskeletal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In contrast, OoC technology can recreate FSS within its microfluidic systems, and when supplemented with ECM components, it can simulate a more realistic internal environment. Studies have shown that PTECs cultured in microfluidic devices exhibit upregulated expression of ZO-1, increased numbers of ciliated cells, and enhanced albumin uptake and degradation (Ferrell et al, 2012;Jang et al, 2013).…”
Section: Proximal Tubule-on-a-chipmentioning
confidence: 99%
“…In contrast, OoC technology can recreate FSS within its microfluidic systems, and when supplemented with ECM components, it can simulate a more realistic internal environment. Studies have shown that PTECs cultured in microfluidic devices exhibit upregulated expression of ZO-1, increased numbers of ciliated cells, and enhanced albumin uptake and degradation (Ferrell et al, 2012;Jang et al, 2013).…”
Section: Proximal Tubule-on-a-chipmentioning
confidence: 99%